Effects of rotor blade-tip geometry on helicopter trim and control response. (10th April 2017) - Kumar, M. Rohin; Venkatesan, C.
ABSTRACT: For performance improvement and noise reduction, swept and anhedral tips have been incorporated in advanced-geometry rotor blades. While there are aerodynamic benefits to these advanced tip geometries, they come at the cost of complicated structural design and weight penalties. The effect of these tip shapes on loads, vibration and aeroelastic response are also unclear. In this study, a comprehensive helicopter aeroelastic analysis which includes rotor-fuselage coupling shall be described and the analysis results for rotor blades with straight tip, tip sweep and tip anhedral shall be presented and compared. The helicopter modelled is a conventional one with a hingeless single main rotor and single tail rotor. The blade undergoes flap, lag, torsion and axial deformations. Tip sweep, pretwist, precone, predroop, torque offset and root offset are included in the model. Aerodynamic model includes Peters-He dynamic wake theory for inflow and the modified ONERA dynamic stall theory for airloads calculations. The complete 6-dof nonlinear equilibrium equations of the fuselage are solved for analysing any general flight condition. Response to pilot control inputs is determined by integrating the full set of nonlinear equations of motion with respect to time. The effects of tip sweep and tip anhedral on structural dynamics, trim characteristics and vehicle response to pilot inputs are presented. It is shown that for blades with tip sweep and tip anhedral/dihedral, the 1/rev harmonics of the root loads reduce while the 4/rev harmonics of the hub loads increase in magnitude. Tip dihedral is shown to induce a reversal of yaw rate for lateral and longitudinal cyclic input.